ANALISIS YURIDIS PUTUSAN NOMOR 1082 K/PDT.SUS-HKI/2022 TENTANG SENGKETA MEREK YANG MEMILIKI PERSAMAAN PADA MEREK MASTERTINT - Adawiyah, Rodiatun; Roymond Eygia, Migel; Arta Yanda Rajagukguk, Wisnu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Brand disputes between the well-known brand "MASTERTINT" and the plaintiff receive legal protection. Legal protection for trademarks is regulated in trademark law number 20 of 2016. Proving the element of similarity in essence or in its entirety is the starting point for the panel of judges' consideration in trademark cases between MASTERTINT which is under COATINGS FOREIGN IP Co. LLC and brands come first. suing Soetrisno's MasterTint brand to the Supreme Court was deemed to have similar elements in essence or in its entirety. This research is a normative legal research method using a case approach which aims to find the legal basis, understanding and rules relating to the use of market survey results to show that brands are not used. Brand legal regulations in the new trademark law number 20 of 2016 have attempted to provide legal protection for brand rights holders. The handling of brand rights violations, which can be done in various ways, should be able to provide protection for brand rights holders.